Candy Girl - McCombie, Karen (Edinburgh, U.K. : Barrington Stoke Ltd., 2010)
Dixie lands a dream work experience placement at Candy magazine, but rather than interviewing celebrities and mingling with models, she spends all her time making tea and reading all the letters from readers, and finds a letter from her own sister asking for advice.
4.2
5-8.
5-8
Keywords: Apprentices -- Juvenile fiction; Periodicals -- Juvenile fiction; Apprentices -- Fiction; Periodicals -- Fiction; Apprentices -- Fiction; Periodicals -- Fiction